Pre and post operative radiological assessment of distal radius fracture - Nikunj C. Desai; Utsav V. Patel (Al Ameen Medical College, 2024)
Background: Distal radius fractures are the most common fractures of upper limb. It accounts nearly 15- 20% of all fractures. Many surgical modalities are available for treatment of the same. It ranges from closed reduction &K-wiring to open reduction & fixation using plates. Objectives: To compare the radiological outcomes of distal radius fractures treated with various operative interventions by parameters like radial inclination, radial height and radial tilt. To find out appropriate modality of management for all varieties of distal end radius fracture. Correlation of the functional and radiological outcomes of various operative modalities and its comparison between different types of fractures. Methods: 110 patients were called for functional and radiological assessment. All the cases were classified according to fracture patterns for comparison of x-rays of operated and opposite wrist joint to analyse the radiological and functional outcomes. Result: Overall 110 patients were operated with slightly male preponderance, 62 male patients (56%) and 48 female patients (44%).Plating had superior outcomes followed by K-wiring. Conclusion: Distal radius fractures are increasingly common. Goal of treating distal radius fracture should be to achieve a painless, congruous wrist joint with anatomic reduction of the fracture along with faster and optimum recovery of functions which can be effectively assessed by radiological parameters.